Systematic Review and Recommendations to Combine Newer Therapies With Conventional Therapy in Psoriatic Disease - Arora, Sandeep; Das, Pankaj; Arora, Gulhima (Frontiers in Medicine, 2021)
Background: Psoriasis continues to have unmet needs in its management despite introduction of newer molecules. Monotherapy with newer agents may not achieve therapeutic goals in all cases, hence necessitating their combinations with other molecules. Improved understanding of newer as well as conventional treatment modalities and experiences in their combinations hence necessitates therapeutic guidelines for their use in psoriasis. Objective: To review the combinations of treatments reported in literature and recommendations for their use based on best current evidence in literature. Methods: A literature review of MEDLINE database for studies evaluating combinations of newer therapies with conventional therapies in psoriasis was done. Newer therapies were identified as biologic disease modifying anti rheumatic drugs and other molecules such as apremilast while conventional therapies included methotrexate, cyclosporine, or retinoids, phototherapy and others. The therapeutic guidelines are proposed with the aim to provide evidenced based approach to combine newer and conventional agents in day-to-day psoriasis management. Findings: Combination of acitretin and narrow band ultraviolet B (NB-UVB)/ Psoralen with ultraviolet A (PUVA) achieves faster clearance and allows reduction of dose of the latter. A variable outcome is reported of methotrexate with TNF-α inhibitors versus TNF-α inhibitors alone, although addition of methotrexate appears to reduce immunogenicity of TNF-α inhibitors thereby preventing formation of anti-drug antibodies especially in case of infliximab. While combination of acitretin and PUVA is beneficial, combining TNF-α inhibitors and phototherapy too produces better and faster results but long term risks of Non Melanoma Skin Cancers (NMSCs) may preclude their use together. Combination of cyclosporine and phototherapy is not recommended due to greater chances of NMSCs. Adding phototherapy to Fumaric Acid Esters (FAEs) improves efficacy. Apremilast can be safely combined with available biologic agents in patients with plaque psoriasis or psoriatic arthritis not responding adequately to biologics alone. Hydroxyurea and acitretin may be used together increasing their efficacy and reducing doses of both and hence their adverse effects. Conclusion: Selected clinical scenarios shall benefit from combinations therapies, improving efficacy of both conventional and newer agents and at the same time helping reduce toxicity of higher dosages when used individually.